Brian B. Schmidt, The Materiality of Power: Explorations in the Social History of Early Israelite Magic. Forschungen zum Alten Tstament 105. Tübingen, Mohr Siebeck, 2016. XV + 258. ISBN 978–3–16–153302–0. €99 - Tebes, Juan Manuel (2017)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina; Argentina